Significant of export performance in international trade: the case of Malaysia External Trade Development Corporation (MATRADE) / Marwan Md.Nor - Md.Nor, Marwan (Faculty of Business and Management, 2009)
The significance of export performance in international organizational in the context of the international economic development can be look over the past two decades whereby exporting has been one of the fastest growing economic activities. Exporting also plays a key role to achieve sustainable competitive advantage of firms in the turbulent market, because of the improvement of financial position, increased capacity utilization, higher technological standards, and attainment of a desired performance. In Malaysia, we have one organization that handle all the export promotion towards Malaysia branding in order to penetrate into international level. Malaysian External Trade Development Corporation (MATRADE) is the national trade promotional agency. MATRADE also assists in trade matching between foreign buyers and Malaysia exporters. MATRADE is the local point for international companies sourcing for Malaysian products and services. The need for further research work discussed in this report. In determining the significant factors which contribute to determining in export performance, some variables are taken to be used in order to measure the most influences factors towards developing Malaysian exporters to export their product to the world which might influences the establishment of MATRADE as one of the government agency who responsible for assisting Malaysian companies succeed in the international market. The selected variables include promotion strategy, networking, and management characteristics. The objective of the study is to evaluate whether the promotion strategy, networking and management characteristics has significant relationship towards export performance. Data collected through questionnaire from the respondents under promotion and development department who directly involved in promotion activities towards Malaysian exporters. There are international network, trade promotion division, exporter’s development division, and product and services development division. By using the Statistical Program Social Science (SPSS), the results from this research show that promotion strategy and networking have moderate relationship towards export performance and management characteristics have strong relationship towards export performance of MATRADE.